Design of shallow foundations using eurocode 7 - Yim, Jen Fie. (2013)
British Codes and Standards (BS) have been used in practice for many years and it is to be replaced by the whole suite of structural Eurocodes. With this replacement, practicing engineers will need to understand the methodology and design philosophy adopted in the new code and also to be familiar with the assumptions made. The complete set of Eurocodes consists of 10 codes, EC to EC9. EC covers the structural basis design, EC1 describes actions on structures and EC2 to EC6 deal with design of materials such as concrete, steel, timber and mansory. EC7 and EC8 cover the geotechnical and seismic design respectively. The main difference of Eurocodes from the other conventional codes is that it uses partial factors for actions, materials and resistances rather than an overall factor of safety. EC7 is the subject in this report and is divided into 2 parts. Part 1 (BS EN 1997-1) - General Rules which lays down the generally adopted geotechnical design application rules and principles to make sure that buildings with foundations are sufficiently strong, stable, durable as well as with little or no deformation. Part 2 (BS EN 1997-2) - Ground Investigation and Testing supplies additional rules to Part 1 that is linked to site investigations planning and common necessity to undergo laboratory and field tests. EC7 proposed three methods for shallow foundation designs, namely direct, indirect and prescriptive method. For the most commonly used direct method, both ultimate limit state (ULS) and serviceability limit state (SLS) have to be checked separately. EC7 allows 1 of the 3 Design Approaches (DA), DA1 to DA3 to calculate for ULS conditions. DA1 will be adopted in Singapore, following the British version of Eurocodes and it will be discussed in detail in this report. In this report, hypothetical case studies are used to illustrate the method of designing strip footing according to EC7. With this, three commonly used geotechnical design codes, British Code BS8004, Hong Kong Code of Practice for Foundation and US Naval Facilities Engineering Command (NAVFAC) are used to make comparison with EC7 using the same case studies.